Pengaruh Kompetensi Dan Kepemimpinan Manager Proyek Serta Produktivitas Tenaga Kerja Terhadap Keberhasilan Proyek - Ganjar Jojon Johari; Rahman Syafrudin (Jurnal Konstruksi, 2026)
Construction projects often face challenges such as inadequate planning, low workforce competence, and ineffective project manager leadership, which can result in schedule delays, cost overruns, and declining project quality. This study aims to analyze the influence of competence, project manager leadership, and labor productivity on the success of the Hotel Rancabango Convention Center construction project in Garut Regency. A quantitative approach was applied using multiple linear regression analysis. Data were collected from 65 respondents through questionnaires using purposive sampling techniques. The F-test results show an F-value of 16.761 with a p-value of 0.000, indicating that project manager competence and leadership have a significant effect, while labor productivity does not have a significant effect on project success. The study concludes that improving competence and strengthening the leadership role of project managers are key factors in achieving construction project success. These findings can be used as a reference for project management strategy planning and for policies aimed at improving human resource quality in the construction sector.